Perjanjian Jasa Pemborongan Pekerjaan Pembangunan Jalan Tol Jakarta-Cikampek II Elevated Ditinjau dari Peraturan Perundang-Undangan di Indonesia - Iwan Dewantoro; Sufiarina Sufiarina; Riana Wulandari Ananto (Jurnal Syntax Admiration, 2024)
The research was conducted with the aim of evaluating the extent to which the clauses in the Design and Build Agreement on the Jakarta-Cikampek II Elevated Toll Road Construction Project are in accordance with the provisions of laws and regulations governing construction services and procurement of goods/services. The research applies the empirical juridical method as a research approach, which is an approach used to analyze the extent to which a regulation or law is effectively applied in society. The data used in this research is primary data, namely data obtained directly from the source in the field, either through observation or informal documents which are then processed by researchers. In this research, primary data is obtained through observation and documents from PT Jasamarga Jalanlayang Cikampek as a Service User and Waskita-Acset KSO as a Service Provider. The results of the study concluded that the Design and Build Agreement Clause for the Construction of the Jakarta-Cikampek II Elevated Toll Road has fulfilled the provisions of Law Number 2 of 2017 concerning Construction Services, but the clause regarding changes to the Contract or Contract Addendum does not meet the provisions of Presidential Regulation Number 54 of 2010 Article 87 paragraph (1).